TECHNICAL EVALUATION OF THE DARWAZA FORMATION IN ENGINEERING AND CHEMICAL INDUSTRIES, KHYBER PAKHTUNKHWA, PAKISTAN: INSIGHTS FROM PETROGRAPHY, GEOTECHNICAL, AND GEOCHEMICAL PROPERTIES - Muhammad Naveed Anjum,; Muhammad Athar,; Muhammad Yaseen,; Muhammad Irfan,; Gohar Rehman, (Spectrum of Engineering Sciences, 2025)
The objective of this research is to conduct a comprehensive geotechnical investigation of the Darwaza Formation at the study site, a Cambrian-aged geological unit predominantly composed of limestone. Petrography and a series of physio-mechanical, chemical, and analytical tests were conducted, including Los Angeles (LA) abrasion, impact strength, specific gravity, water absorption, soundness testing, scanning electron microscopy (SEM) with attached energy dispersive X-ray spectroscopy (EDX). Petrographic analysis of the Darwaza Limestone unit under polarized light microscopy reveals that the limestone is largely micritic to sparitic in texture, with varying degrees of recrystallization. The primary constituents include calcite, with minor occurrences of dolomite in some samples. The calcite in the Darwaza Limestone exhibits neomorphic textures, indicating diagenetic alteration of the original micritic material. Mineralogical characteristics and textural features were correlated with physio-mechanical properties to validate the laboratory results. The physio-mechanical properties (e.g., LA =20.9%, Soundness = 2.0%) and Impact value test = 12.1%), of the Darwaza Formation are found to fall within acceptable standard limits of ASTM. Based on these findings, it is proposed that the limestone of the Darwaza Formation is suitable for engineering applications and can be effectively used as construction aggregate. Beyond its suitability for the construction industry, the high calcium carbonate (CaCO₃) content—exceeding 95% also supports the potential use in paper, glass, sugar, ceramics, adhesives, food and pharmaceutical industries.